STUDI KUANTITATIF: BIAYA TRANSAKSI DALAM PERSPEKTIF MANAJEMEN PEMERINTAHAN DI INDONESIA - Arie Purnomo (Jurnal Noken: Ilmu-Ilmu Sosial, 2017)
The research aim to know the transaction cost in government management prospective consist of the government cost and market cost with suitable the government service in government management prospective. The result of government in applied of transaction cost have affect by the government cost suitable with routine cost, development cost, human resource cost and facility cost suitable with information, administration, operational and technology costs in applied the suitable of service with principle, accountable, leadership, productivity and service quality. The appointment of market cost have positive toward transaction cost for several activity or job program in government scope. The government instance have responsibility in appointment of transaction cost with give of propose planning suitable with need of government in applied of information, administration, operational and technology cost which affected toward suitable of service. Although the transaction cost in specific occured with the transaction cost particularly relate with cost transaction because the government cost require to suitable with transaction cost.Â